The Performance of Squeeze Film between Parallel Triangular Plates with a Ferro-Fluid Couple Stress Lubricant - Toloian, Akbar; Daliri, Maghsood; Javani, Nader (HINDAWI LTD, 2020)
The present study aims at investigating a couple stress ferrofluid lubricant effects on the performance of the squeezed film when a uniform external magnetic field is applied. For this purpose, Shliomis ferrohydrodynamic and couple stress fluid models are employed. The considered geometry is parallel triangular plates. The effects of couple stress, volume concentration, and Langevin parameters on squeeze film characteristics including time vs. height relationship and load-carrying capacity are investigated. According to the results, employing couple stress ferrofluid lubricant in the presence of the magnetic field leads to an increased performance of the squeeze film.
Keywords: INERTIAL FLUIDS; VISCOSITY; EQUATION; Engineering